Forming the ideas of tolerance in educational thought of Ukraine: the source studies aspect (Pedagogy of Higher and Secondary Education, 2016)
Motuz T. V. Forming the ideas of tolerance in educational thought of Ukraine: the source studies aspect.An analytical review and classification of source database of research of ideas of tolerance in educational thought of Ukraine are given in this article. The sources are identified and systematized in four groups, and represent the sequence of scientific development of the research problem.They are normative sources (legislative materials of international, national, regional levels: declarations, laws, resolutions, orders etc.); scientific-pedagogical sources (monographs, articles, historical researches, dissertations for the doctor’s and candidate degree); methodical literature (tutorials, recommendations, which are developed by pedagogical staffs of educational institutions of different types, generalization of experience, reports, materials of congresses, conferences); sources of personal origin: memoirs (memories and autobiographies) and works of fiction. Representation of formed sources is based on source-grounded analysis and synthesis taking into accounts the socio-cultural context.We were guided by the following principles to select sources for analysis: аuthenticity (information contained in selected sources is not only versatile and complete, but authentic); сomplementarity (primary data coming from different sources must be mutually complemented, varied and most fully reflect all aspects of the research subject); сonsistency (to make theoretical generalizations sources should enable systematic coverage of the most significant facts).The complex of historical and educational resources and literature, which are worked out in the research process, includes all the possible ways of obtaining information that enables to make the system analysis and generalization of the research problem. The analysis of studied sources shows that they are quite reliable and sufficient for the theme.The systematization of source database of the research the history of ideas of tolerance in educational thought of Ukraine, presented in article, allows considering the development of various aspects of the research problem in dynamics from a theoretical study to practical implementation.
Keywords: исторический источник; педагогический источник; источники актированного характера; научно-педагогические источники; толерантность; классификация